2015
DOI: 10.1111/cxo.12237
|View full text |Cite
|
Sign up to set email alerts
|

Rigid gas‐permeable contact lens related life quality in keratoconic patients with different grades of severity

Abstract: Purpose The aim was to compare the impact of rigid gas‐permeable (RGP) contact lenses on vision‐related quality of life (VR‐QOL) in keratoconic patients with different grades of severity. Methods This comparative study was conducted from December 2012 to September 2013 on 46 patients with bilateral keratoconus. Patients were divided into three groups according to the average of the steep keratometry (K) readings in the two eyes of each patient. Main outcome measures included binocular visual acuity (VA), lens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 26 publications
1
42
1
Order By: Relevance
“…Wu and colleagues investigated RGP contact lens‐related life quality in keratoconic patients with different grades of severity. They showed that patients with mild and moderate keratoconus were able to achieve a sufficient lens wearing time (mean: 10.4 hours per day; 9.6 hours per day, respectively), whereas the severe keratoconic patients showed a significantly reduced wearing time (mean: 4.8 hours per day).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wu and colleagues investigated RGP contact lens‐related life quality in keratoconic patients with different grades of severity. They showed that patients with mild and moderate keratoconus were able to achieve a sufficient lens wearing time (mean: 10.4 hours per day; 9.6 hours per day, respectively), whereas the severe keratoconic patients showed a significantly reduced wearing time (mean: 4.8 hours per day).…”
Section: Discussionmentioning
confidence: 99%
“…If the ordered lenses gave an acceptable fit, vision and comfort, the patient was scheduled for the next visit. Patients were asked to grade the performance of RGP lenses using a Likert scale 15,16 (in which 1 represents very poor and 5 represents excellent) with respect to foreign body sensation, comfort and overall satisfaction preoperatively and three and six months after the CXL procedure. Additionally, regarding lens wearing time, patients were asked to state how many hours a day they had been wearing the lenses.…”
Section: Corneal Aesthesiometrymentioning
confidence: 99%
“…There are several options such as rigid gas-permeable (RGP) contact lenses (5), hybrid contact lenses (6), piggyback lenses (7) and scleral contact lenses (8). RGP lenses are traditionally first choice because of their success in improving visual acuity (9) RPG lenses improve visual acuity by their refractive power and also by flattening the anterior cornea, increasing the thinnest corneal thickness, and reducing anterior surface high-order aberrations (3,4). Previous studies showed that RGP contact lenses provide a significant improvement in visual acuity compared to spectacles-corrected visual acuity in patients with high corneal astigmatism (10), and keratoconus (11).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that RGP contact lenses provide a significant improvement in visual acuity compared to spectacles-corrected visual acuity in patients with high corneal astigmatism (10), and keratoconus (11). Previous studies also showed that an appropriate use of RGP contact lenses contributes to good vision-related quality of life for keratoconic patients (9).…”
Section: Introductionmentioning
confidence: 99%
“…Some early signs [2,3] of keratoconus are asymmetric refractive error with high or progressive astigmatism, keratometry showing high astigmatism and irregularity, scissoring of the red reflex on retinoscopy, and inferior steepening. The vast majority of keratoconus patients can be visually rehabilitated with glasses or rigid gas permeable lenses [4] (RGPs). In only a small percentage of keratoconus patients is a cornea transplant needed.…”
Section: Introductionmentioning
confidence: 99%